(untitled) (Research, Society and Development, 2025)
This study presents a bibliometric analysis on postharvest fruit quality, aiming to identify trends, research gaps, and innovations within the field. Using bibliometric methods, 1,311 publications from 2010 and december of 2023 were selected based on specific criteria and analyzed through tools like VOSViewer and Bibliometrix to map collaborations, citations, and relevant keywords. The study highlights the growing importance of sustainable practices and technologies to ensure the longevity and quality of agricultural products. The analysis indicates that innovations such as edible coatings and natural antioxidants, along with the use of biosensors and artificial intelligence, hold significant potential for enhancing fruit conservation and reducing losses. Additionally, the findings underscore that international scientific collaboration—especially among emerging and developed countries, with China and Brazil leading in publications and partnerships—drives progress in the sector, strengthening food security and the sustainability of agricultural supply chains. The study further reveals that integrated strategies, such as climate-smart agriculture, are essential for reducing losses, bolstering food security, and promoting more sustainable supply chains. These findings not only contribute to guiding future research but also provide a basis for public policy on postharvest conservation, essential for addressing global challenges related to food waste and climate change.